Pengelolaan Wakaf Uang Melalui Aplikasi Fintech Pada Koperasi Syariah Di Kota Bandung - Nurjamil; Siti Nurhayati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
This study aims at providing an insight into the legal status of waqf through application in fintech pursuant to Law No41 of 2004 and Law no 11 of 2008 on Information and electronic transactions, a form of nadzir responsibility for managing waqf assets through fintech applications and then seeking a model for the economic empowerment of individuals through through the use of fintech applications. The method employed in this study is a method of regulation, referring to qualitative legal research. The results found that the application of fintech applications in the management of cash waqf is not specifically governed by Waqf or ITE Law, but still permitted as long as the applicable law is not in contravention. In the management of waqf nazhir, the management of waqf properties shall be responsible and legal proceedings can be taken in the event that waqf property is lost due to negligence. In collaboration with Bandung's city of fintech companies, the sharia cooperative registered as Nazhir waqf cash is owned only by KSPPS BMT ITQAN where, in the form of SME finance for members based on waqf funds, the model of waqf management is used through the Rumah Pembiayaan Majelis (RPM) empowerment program, based on a fintech application called itQanmobile and kitawakaf.com, a social crowdfunding platform fintech